MEKANISME PENJATUHAN SANKSI PEMBERHENTIAN NOTARIS DENGAN TIDAK HORMAT - Anugerah, Fahmi Mahdi; Azizurrahman, Syarif Hasyim; Suasono, Edy (Faculty Of Law, Universitas Tanjungpura, 2023)
AbstractThe purpose of this research is to explain the mechanism for imposing sanctions for dishonorable discharge and to analyze the considerations of the Notary Supervisory Board in imposing sanctions for Disrespectful Dismissal. The research method used is an empirical juridical research method. The data collection technique used in this research is secondary data. The results of the research are that the mechanism for imposing sanctions for dishonorable dismissal starts from an examination carried out by the Regional Examining Council, the results will be submitted to the Regional Supervisory Council and will be re-examined by the Regional Examining Council, and the Regional Supervisory Council proposes sanctions for Disrespectful Dismissal to the Central Supervisory Council, then it will The proposal for dismissal is re-examined by the Central Auditing Council, and after that the Central Supervisory Council submits a proposal for the sanction of Disrespectful Dismissal to the Minister of Law and Human Rights for decision. Things that are taken into consideration by the Notary Supervisory Board in imposing sanctions for Disrespectful Dismissal are violations of the notary's obligations and prohibitions as well as the presence of criminal elements in the violations committed by the notary. Abstrak Tujuan penelitian ini adalah untuk menjelaskan bagaimana mekanisme penjatuhan sanksi pemberhentian tidak hormat dan menganalisis pertimbangan Majelis Pengawas Notaris dalam menjatuhkan sanksi Pemberhentian Tidak Hormat. Metode penelitian yang digunakan adalah metode penelitian yuridis empiris. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah data sekunder. Hasil penelitian adalah mekanisme penjatuhan sanksi pemberhentian tidak hormat dimulai dari pemeriksaan yang dilakukan Majelis Pemeriksa Daerah, hasilnya akan disampaikan kepada Majelis Pengawas Wilayah dan akan diperiksa kembali oleh Majelis Pemeriksa Wilayah, dan Majelis Pengawas Wilayah mengusulkan sanksi Pemberhentian Tidak Hormat kepada Majelis Pengawas Pusat, selanjutnya akan diperiksa kembali usulan pemberhentian tersebut oleh Majelis Pemeriksa Pusat, dan setelah itu barulah Majelis Pengawas Pusat memberikan usulan sanksi Pemberhentian Tidak Hormat kepada Menteri Hukum dan Hak Asasi Manusia untuk diputuskan. Hal yang menjadi pertimbangan Majelis Pengawas Notaris dalam penjatuhan sanksi Pemberhentian Tidak Hormat adalah adanya pelanggaran terhadap kewajiban dan larangan notaris serta adanya unsur pidana dalam pelanggaran yang dilakukan notaris.